Penerapan SISKEUDES Berbasis Cash Management System Dalam Meningkatkan Akuntabilitas Keuangan Desa - Ulandari, Bq Dini Ulandari; Martiningsih, Rr. Sri Pancawati (Kajian Ekonomi dan Bisnis, 2025)
This study aims to explore the implementation of SISKEUDES that emphasizes the Cash Management System (CMS) to improve village financial accountability in Wanasaba Lauk Village, Wanasaba Sub-district, East Lombok Regency. The approach used in this research is descriptive qualitative method. Data collection methods in this study were conducted by observation, interview, and documentation. The informants in the study were the village head, the village treasurer, and the head of planning affairs. The research findings show that the implementation of CMS-based SISKEUDES in Wanasaba Lauk Village has been running well according to the principles of village fund management regulated by the Permendagri Number 20 year 2018. However, there are still problems or shortcomings. Furthermore, regarding accountability assessed by vertical and horizontal accountability indicators, it can be stated that it is increasingly accountable. This study is expected to contribute to expanding readers' knowledge about the implementation of a cash management system-based village financial system. The limitation of this study is that it only examines the implementation of a CMS-based village-level financial system in Wanasaba Lauk Village, Wanasaba Sub-district, East Lombok, so the findings obtained cannot be generalized to other locations.